Critical path of women in situations of intimate partner violence - Daniella Yamada Baragatti; Diene Monique Carlos; Maria Neto da Cruz Leitão; Maria das Graças Carvalho Ferriani; Eliete Maria Silva (Universidade de São Paulo, 2018)
ABSTRACT Objective: To know and analyze the critical path followed by women subjected to intimate partner violence until reaching a Reference Center of a Brazilian city, from the perspective of these women. Method: Qualitative research, based on the concept of critical path. Participant observations of the support group of the Reference Center and interviews with ten women in situations of violence who were followed up in this service. Results: the motivating factors for women to seek help were the increase in the severity of the aggressions, the impact of the violence on their children and support from their family. They go to several sectors and services before reaching the Reference Center, such as the police and legal counsel, health and social services. They find little effective responses from the services, and care is indicated as the most relevant response factor to face the situation. Conclusion: the assistance is fragmented and dependent on the posture of the professional. The Reference Center is recognized as an important place of support for women. In addition to governmental efforts to maintain the network structured, the permanent education of the working professionals is also fundamental.